2018
DOI: 10.1371/journal.pone.0197301
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance-adjusted creatinine at initiation of continuous venovenous hemofiltration and mortality. A post-hoc analysis of a multicenter randomized controlled trial.

Abstract: IntroductionAcute kidney injury (AKI) requiring renal replacement therapy (RRT) is associated with high mortality. The creatinine-based stage of AKI is considered when deciding to start or delay RRT. However, creatinine is not only determined by renal function (excretion), but also by dilution (fluid balance) and creatinine generation (muscle mass). The aim of this study was to explore whether fluid balance-adjusted creatinine at initiation of RRT is related to 28-day mortality independent of other markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The current recommendations for staging AKI use easily ascertainable and widely available surrogates of kidney function. 8,12 In this context, the criteria for staging AKI according to the KDIGO guideline, urine output adjusted for actual body weight [13][14][15] and measured sCr, [16][17][18][19][20] are the focus of current scientific discussions. In line with this ongoing debate and to establish a basis for possible future research, this study comprehensively analyzed mainly the adjustment of urine output by PBW as well as various other adjustments of the current recommendations for staging AKI in a large collective of patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The current recommendations for staging AKI use easily ascertainable and widely available surrogates of kidney function. 8,12 In this context, the criteria for staging AKI according to the KDIGO guideline, urine output adjusted for actual body weight [13][14][15] and measured sCr, [16][17][18][19][20] are the focus of current scientific discussions. In line with this ongoing debate and to establish a basis for possible future research, this study comprehensively analyzed mainly the adjustment of urine output by PBW as well as various other adjustments of the current recommendations for staging AKI in a large collective of patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SCr is not only determined by renal function (excretion), but also by hemodilution (caused by fluid accumulation). It is reported that lower SCr levels caused by fluid overload may underestimate true renal function impairment in critically ill patients [30]. The lack of cumulative fluid balance due to the retrospective nature of the study design may cause information bias.…”
Section: Discussionmentioning
confidence: 99%